Frequency of Common Risk Factors of Recurrent Diabetic Diabetic Metabolic Acidosis among Children - Wasim Abbas, Farman Ullah, Asfand Tariq, Taj Muhammad, Nighat Jabeen, Zarmast Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic metabolic acidosis (DKA) is a serious dilemma for diabetics that arises when the body cannot create sufficient insulin. associated withboth the main subtypes of diabetes. It is characterized by an elevation in blood glucose concentrations, combined with the presence of ketones and acidosis symptoms. The frequency of DKA episodes among children with T1DM can vary widely depending on several factors, such as age and duration of the disease, adherence to treatment regimens, frequency of medical visits, and access to health care. The frequency of common risk factors for recurrent DKA has not been well studied. Objective: To estimate the prevalence/frequency of common risk factors of recurrent Diabetic metabolic acidosis in infancy,toddlers,preschoolers and teenaged with diabetes. Method: This epidemiological study explored the relationship between Type 1 Diabetes Mellitus (T1DM) and risk factors associated with life-threatening recurrent diabetic metabolic acidosis. Careful examination of medical records, laboratory results, physical exams and more were conducted on 0-18 year old children admitted to a public reference/tertiary care hospital in Pakistan over one year's time.Through bivariate and multivariate Poisson regression analysis, researchers sought to uncover patterns in age groups as well as doctor visits frequencies rate and treatment plans related to T1DM development among infancy, toddler hood through preteen years. Results: Our study of 456 patients uncovered a connection between infections, consistent healthcare visits, following prescribed medication instructions, and DKA episodes. Significantly higher rates of multiple DKA incidents were observed among those who had missed one or more medical appointments compared to regular attendees. Of the participants surveyed 63% reported taking their medication as instructed while 24% admitted to missing doses or not heeding dosage directions correctly. These results emphasize that proper management is key in preventing severe health complications such as diabetes-related acidosis attacks for diabetes sufferers worldwide Conclusion: Our data suggest that recurrent DKA in children with T1DM can vary significantly based on numerous factors, including age, disease duration, medical visit frequency, and medication adherence. Therapies may be able to alleviate this. To understand the impact of recurrent DKA rates in T1DM children, additional research is required. Keywords: Frequency of common risk factors; recurrent diabetic diabetic metabolic acidosis; children with type 1 diabetes mellitus